2012
DOI: 10.1644/11-mamm-a-241.1
|View full text |Cite
|
Sign up to set email alerts
|

The diet, prey selection, and activity of dholes (Cuon alpinus) in northern Laos

Abstract: Although Southeast Asia is one of the last strongholds of endangered dholes (Cuon alpinus), or Asiatic wild dogs, little is known about dhole ecology in this region. We used scat collections, prey surveys, and camera-trap data to determine the diet, prey selection, and activity of dholes in a national protected area in northern Laos. Results showed that dhole diets were dominated by ungulates (87% of biomass consumed), with additional prey including other carnivores (6%) and rodents , 1 kg (6%). Concerning ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 30 publications
5
41
0
1
Order By: Relevance
“…Our results highlight the importance of medium to large-sized prey for driving dhole occupancy across the landscape, in concordance with other studies of dhole feeding ecology in the Western Ghats and across Asia [12], [13], [19], [20], [78].…”
Section: Discussionsupporting
confidence: 92%
“…Our results highlight the importance of medium to large-sized prey for driving dhole occupancy across the landscape, in concordance with other studies of dhole feeding ecology in the Western Ghats and across Asia [12], [13], [19], [20], [78].…”
Section: Discussionsupporting
confidence: 92%
“…For example, Kawanishi and Sunquist (2008) report that, in Malaysia, Cuon alpinus mostly preys upon mouse deer (Tragulus kanchil, body mass about 2-4.5 kg). By contrast, Kamler et al (2012) demonstrated a preference for larger prey in Laos, such as muntjac deer (Muntiacus) or sambar deer (Rusa unicolor), with an average prey body mass of 75-85 kg, as well as the occurrence of other carnivore remains in dhole scats. Sambar deer seems to be the most common prey in central India while dholes in the southern regions seem to prefer axis deer (Axis axis) (Kamler et al 2012).…”
Section: Introductionmentioning
confidence: 98%
“…By contrast, Kamler et al (2012) demonstrated a preference for larger prey in Laos, such as muntjac deer (Muntiacus) or sambar deer (Rusa unicolor), with an average prey body mass of 75-85 kg, as well as the occurrence of other carnivore remains in dhole scats. Sambar deer seems to be the most common prey in central India while dholes in the southern regions seem to prefer axis deer (Axis axis) (Kamler et al 2012). The preferences of dholes for different kinds of prey could be related to human action but could also be due to other carnivore antagonisms, as we will discuss subsequently.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Initially this resulted in broad classification of taxa as diurnal, nocturnal, crepuscular, or cathemeral (van Schaik and Griffiths, 1996). More recently, researchers have compared activity patterns among species to see how overlapping patterns may relate to competition or predation (Linkie and Ridout, 2011;Carver et al, 2011;Ramesh et al, 2012;Carter et al, 2012;Kamler et al, 2012;Ross et al, 2013;Azevedo et al, 2018). Ridout and Linkie (2009) presented methods to fit kernel density functions to times of observations of animals and to estimate the coefficient of overlapping, a quantitative measure ranging from 0 (no overlap) to 1 (identical activity patterns).…”
Section: Introductionmentioning
confidence: 99%